Do preço ao apreço: um estudo sobre a construção do mercado de CSA (Comunidade que Sustenta a Agricultura) no Brasil - Paiva, Caroline Mendonça Nogueira (2019)
Marketing has incorporated in its studies the field of Constructivist Market Studies. This field is based on understanding that markets are constantly developing thanks to the actors that operate in it. Under this perspective, markets can and should be studied, eventually creating several theories to explain their behaviour, such as Market Practices and the Marketization Program. The market consists of three sets of practices: Representational practices, Normalizing practices and Exchange practices. It also configures itself through five frames: Pacifying goods; Marketizing agencies; Market encounters; Price-setting; and Market design and maintenance. As it is not possible to achieve the full frames, overflows occurs, which alter the structures that make up the market, resulting in its dynamics. The association between practices and frameworks allows actors to perform different calculations in the markets, which will be decisive in making transactions. Constructivist Market Studies have been applied in the analysis of alternative agri-food markets to explain that the constituent relations of these markets are much more complex than just the supply of food, also involving technical and social elements to be explored. It is from these elements that different calculations will be performed, bringing their own dynamics to these markets, which differentiate them from conventional markets. In this scenario, emerges the Community Supporting Agriculture - CSA, which was chosen as the object of this study. CSA is an alternative food distribution market, in which farmers and consumers come together to support the agricultural organism in exchange for food supply, based on its singular philosophical structure that differs from other markets. From these conceptual fields, this paper aims to describe, from the perspective of Constructivist Market Studies, how the CSA market is built. As also identify how market practices contribute to the formation of frames in these markets, and how together, practices and frames contribute to the calculation processes. The phenomenon of the construction of the CSA market in Brazil was studied. Therefore, qualitative techniques for data collection, such as interviews, observation and document analysis, which had the collaboration of 28 actors, being members of 7 CSAs and CSA Brasil entity were used. From the content analysis of the data obtained, the main actors and devices that act in the CSAs were identified, as well as the practices that make up these markets, as it follows: i. Representational Practices: Care for the earth and the environment; Commitment; Connection with food; Connection with self and other; Beware of food; CSA philosophy; ii. Normalizing Practices: CSA Brazil training course; Standards and bylaws of each CSA; Production methods and certification standards; Public policy and legislation; iii. Exchange Practices: CSA process management; Agricultural Organism process management; Basket of Products; Consumption. Having identified the practices and their relationships in the context of the communities, the relationship between the practices and the market frames was contextualized, characterizing the configuration of the CSA markets. The analysis also allowed to identify some overflows that happened in the daily life of the communities. Finally, it was possible to identify that in the studied CSAs, the calculation processes are based on calculation, qualculation and calqulation, according to the triad developed by Cochoy (2008) and by a fourth element of value calculation, based on the philosophy that governs the communities: Appreciation. Given this, this thesis contributes to the theoretical advance in the field of Market Building, demonstrating how the processes of formatting alternative markets take place in a dynamic perspective.